Open Innovation Maturity in Companies - Makkonen, Pekka; Siakas, Kerstin; Lampropoulos, Georgios; Brusila-Meltovaara, Kristiina (Academic Publishing, 2023)
Using open innovation approach instead of closed innovation approach improves productivity. To successfully implement the open innovation approach in a company, it is important to evaluate its maturity and readiness to use this approach. The aim of this study is to explore the open innovation maturity and readiness of Finnish and Greek companies. Hence, this study follows a quantitative approach and uses a 13-item survey to explore the open innovation maturity levels. A total of 81 participants from different companies and with different expertise and backgrounds participated in the survey. In addition to the survey, to examine the open innovation maturity of the companies the maturity model for open innovation which consist of five levels with level 5 depicting the highest maturity level was used. The aim was to examine the open innovation maturity of the companies participating in the study. Based on the results, the studied companies were found to mainly achieve level 3 regarding open innovation thinking. More attention and effort should be given to achieve levels 4 and 5. Due to the importance of achieving maturity levels 4 and 5 and their complexity, the need for companies to understand the significance of strategic thinking and for aligning their general strategy with their innovation strategy was highlighted. Additionally, it was evident that to achieve higher levels of maturity, open innovation approaches should be followed and changes in the organizational management should be implemented. Concluding we claim that for companies to adopt an effective open innovation culture, it is essential to integrate appropriate models, methods, and practices starting from lower maturity levels.
Keywords: Open innovation; Maturity; Companies; innovation (activity)